Diversidade genética na cultivar de uva Itália (Vitis vinifera L.), utilizando marcadores microssatélites - Maia, Silvia Helena Zequim (2009)
Genetic diversity in Simple Sequence Repeats (SSR) loci, also known as microssateilites, was estimated iii clones of cultivar Italia (Vitis vinfera L.) in the regions neighboring Marialva, Paiçandu and Urai (Paraná, Brazil) and in the regions around Jales, Pilar do Sul and São Miguel Arcanjo (São Paulo, Brazil). Thirty-six alicIes and 2.12 alleles/polymorphic loci were registered in six populations of cultivar Italia evaluated by primers for 17 SSR loci. Whereas 3 alIcies were reported in loci Vvs3 and Udv96 m six populations of cultivar Italia, only two different alieles were registered for the other 15 loci (Sculüvv, Scullvv, Scul5vv, Udv26, Udv32, Udv34, Udv4O, Udv44, Udv74, Udv85, UdvlO7, UdvlO8, VvmdO5, VvmdO6, VvmdO7). Variable frequencies of alieles in 52.8% of SSR loci provided a high proportion of heterozygote plants iii six populations. Although mean heterozygosity ranged between 0.70 (Paiçandu population) and 0.9647, it was highest in the São Miguel population (H= 0.9647). Expected mean heterozygosity ranged between 0.4064 (Uraí population) and 0.4950; the highest was in the Jales population (F1 = 0.495 0). Parameters of genetic diversity provide an overail excess of heterozygosis (negative rates of F for ali SSR loci anaiyzed). Overali rate of F was -0.8492; it was highest (F -1.0) in loci Sculüvv, Scullvv, Udv26, Udv32,Udv34, Udv4O, Udv85 and Vvmd27. Genetic divergence among the six populations ofthe cultivar Italia was slight 0.0648). Clones cultivated in Jales (SP) and in Uraí (PR) were the most polymorphic ones (52.9%) due to the fact that the clones had the highest proportions of SSR loci with variations in alicie frequencies and a higher divergence in allele frequency. They aiso formed new alieles. Since clone cuitivated in Marialva (PR) showed the lowest SSR loci with variation in alicie frequency (17.6%), a high genetic stability is evidenced, even though it had the highest proportion of chimera plants. The latter shows a higher potential to disseminate genetically divergent clones tbrough vegetative propagation. Current analysis showed that in spite of the fact that Italia clones are reproduced by vegetative propagation, they are not genetically uniform. lii fact, eaeh elone lias genetie variability determined by the rise of new alieles (mutations and/or mitotie recombinations) and by changes iii the frequencies of the original alieles (mitotic recombinations) Key words: Vitis vinjfera, microssateilites, genetie diversity, mitotic recombinations, chimera plants.